Analysis of the Relevance of the Application of Taklifi and Wadh'i Laws in Modern Islamic Economics - Ahmad Fathul Huda; Oman Fathurrahman SW (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to analyze how the roles of Hukum Taklifi and Wadh’i can be applied in establishing Islamic economic law and their relevance to modern economic transactions. Hukum Taklifi provides moral guidance by defining obligations, prohibitions, and allowances in the economic context, such as the obligation to pay zakat and the prohibition of usury (riba). Meanwhile, Hukum Wadh’i regulates the conditions for the validity of economic transactions, including contract clarity and asset ownership. Through a case study of the application of these laws in murabaha contracts within Islamic banking, this research highlights that these laws not only ensure the validity of transactions but also play a crucial role in maintaining fairness and transparency in the modern Islamic financial system. A descriptive approach using library research methods is employed, focusing on Islamic jurisprudence literature to provide an overview of how Taklifi and Wadh’i can contribute to the establishment of Islamic economic law in the contemporary era.